Superadded aspergillosis on carcinoid bronchial adenoma leading to delayed diagnosis. Issue 781 (November 1990) - Kumar, L.; Singh, M.; Mitra, S. K.; Bannerjee, C. K.
Abstract : A review of aspergillosis in neoplastic disease revealed that most cases occur in association with malignant disorders. Amongst solid tumours it is mostly adenocarcinomas which are invaded by the fungus due to necrotic cavity formation. We here record the first reported association of aspergillosis with a benign carcinoid bronchial adenoma which was hidden by the fungal growth with a delay in diagnosis.